Systems approach for assessment of maternal deaths in Rajasthan: A feasibility study. (30th September 2020) - Raghav, P; Gupta, M K; Rustagi, N; Mishra, N; Garg, S
Abstract: Background: High maternal mortality in the state like Rajasthan, which is at second rank in terms of high Maternal Mortality Ratio (MMR) in India, require concentrated efforts in this direction The objectives of this study were to assess the magnitude and trend of maternal death and underlying factors contributing to maternal deaths in Rajasthan and to identify barriers and challenges in reporting maternal deaths in Rajasthan. Methods: Data related to maternal deaths, cause of deaths and live births were retrieved from official Government sources and MMR was calculated. To find out the underlying factors contributing to maternal deaths, Verbal Autopsies were conducted through household surveys. In-depth interviews of health care staff were conducted to carry out the 'SWOT' analysis in order to identify the barriers in reporting maternal deaths. Data was analysed using SPSS version 23. Results: A total of 7185 maternal deaths were reported from Rajasthan in last five years. The mean age of mothers was 25.18±4.98 years. Haemorrhage were reported as most common cause of maternal death (17%) followed by Severe hypertension or fits (8%) and obstructed labour (2%). The median duration of hospital stay was 23 hours (IQR=7.5-70). Maximum deaths were reported during post-partum period (61%), while around one fourth of the deaths happened during delivery. Conclusions: The discrepancies were observed in the reporting of number and causes of maternal deaths. The trend and forecasted figures were quite different from the published National and State level reports in this regard. Key messages: need to streamline and strengthen the Maternal Deaths Surveillance and Response to track the number of deaths and get the exact information about the underlying factors contributing to them. Effective strategies can be developed to reduce the Maternal Deaths in the State.